Pengaruh Infrastruktur Jalan, Tenaga Kerja, dan Investasi terhadap Produk Domestik Regional Bruto di Provinsi Jawa Tengah - Todi Pinandita; Sodik Dwi Purnomo; Heris Kencana Trisna Jaya (Universitas Batanghari Jambi, 2026)
Regional economic development is a strategic step to improve community welfare and strengthen regional economic activity. Gross Regional Domestic Product (GRDP) serves as the primary indicator of economic performance, which is influenced by the availability of infrastructure, labor, and capital. This study aims to analyze the effect of road infrastructure, labor, and domestic direct investment (DDI) on GRDP in Central Java from 2017 to 2025. The research methodology utilizes multiple linear regression with panel data. The results show that road infrastructure, labor, and investment have a negative and significant effect on the GRDP of Central Java Province from 2017 to 2025. These findings imply that local governments are advised to focus on improving road quality, developing human resource competencies, and creating a conducive investment climate